PENGARUH KEPEMIMPINAN TRANSFORMASIONAL DAN BUDAYA KESELAMATAN TERHADAP KINERJA KARYAWAN (STUDI KASUS PT. GERBANG MAS BERSAMA BANDUNG) - Siti Maryam, Shabrina; Muhardi; Nurhayati, Nunung (FEB Universitas Sam Ratulangi Manado, 2023)
The purpose of this study is to identify and examine the parts that result in increased employee performance, namely the transformational leadership factor and the safety culture factor. The method used in this research is descriptive and verification quantitative methods. The population of this study were employees of PT Gate Mas and Bandung. Sampling was carried out using saturated samples. The results of this research are transformationalleadership at PT. Gerbang Mas Bersama Bandung as a whole from various aspects is in the good category. Safety culture at PT. Gerbang MasBersama Bandung as a whole from various aspects is in the good category. Employee performance at PT. Gerbang Mas Bersama Bandung as a whole from various aspects is in the very good category. Transformational leadership has a significant positive impact on employee performance.Safety culture has a positive but not significant effect on employee performance. Transformational Leadership and Safety Culture at PT. Gerbang Mas Bersama Bandung has a significant effect on employee performance